IMPLEMENTASI ADMINISTRASI GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMKN 7 BALEENDAH BANDUNG - Ade Tutty Rokhayati Rosa; Syifa Fauziyah; Aini Insani Dangiangsari; Dewi Setiawati; Aprilia Nazyaati Nadiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher administration is an important aspect in supporting the improvement of educational quality because it plays a role in managing various learning activities effectively and efficiently. Proper implementation of teacher administration can help improve the quality of the learning process, support teachers’ professional duties, and create a more organized learning environment. However, in practice, various obstacles are still found in managing teacher administration, thus further studies regarding its implementation in schools are needed. This study aims to describe the implementation of teacher administration in improving educational quality at SMKN 7 Baleendah, Bandung Regency. This study employed a qualitative approach using a descriptive case study method. Data collection techniques were carried out through observations, interviews, and documentation involving parties related to the implementation of teacher administration in schools. The results of the study indicate that the implementation of teacher administration at SMKN 7 Baleendah, Bandung Regency has been carried out through the preparation of learning tools, management of student administration, implementation of learning assessments, completion of learning journals, and utilization of information technology in teacher administrative activities. Structured implementation of teacher administration has a positive impact on the effectiveness of the learning process and the improvement of educational quality in schools. The study concludes that teacher administration plays an important role in supporting educational quality improvement through systematic, planned, and integrated management of learning activities.